The Role of Zakat in Human Development - Khairul Azhar Meerangani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: Zakat is one of the major economic sources for Islamic countries. The efficiently and systematically of zakat management able to propel it’s potential as an instrument of human development especially among Muslims. The optimum utilization of zakat funds is essential to improving the quality and potential of every Muslim. In Malaysia, zakat is administrated by the Islamic Religious Council (IRC) in every state. The IRC is responsible for determining the beneficiary's qualification and the type of relief that is appropriate based on the background of each recipient so that the relief can be utilized to fulfill their needs. This study aims to assess the potential of zakat in developing the quality of Muslims in Malaysia by highlighting the practice of each IRC in distributing relief to each qualified zakat recipient. The distribution statistics and the form of programs provided by the IRC were analyzed descriptively to see the potential of zakat itself practically in improving the quality of Muslims. The study found that the IRC has provided various programs aimed at improving the quality of asnaf through equitable distribution of economics, social welfare distribution, human capital production and upgrading of education. Thus, every Muslim, especially zakat payers, should take the opportunity to equally engage with the IRC to ensure that zakat funds can be optimized for the development of Muslims in Malaysia.Keywords: Zakat, Human Development, Collection, Distribution, IRC Abstrak:Zakat adalah salah satu sumber ekonomi utama bagi negara-negara Islam. Pengelolaan zakat yang efisien dan sistematis dapat mendorong potensi itu sebagai instrumen pengembangan manusia terutama di kalangan umat Islam. Pemanfaatan dana zakat yang optimal sangat penting untuk meningkatkan kualitas dan potensi setiap Muslim. Di Malaysia, zakat dikelola oleh Dewan Agama Islam (IRC) di setiap negara bagian. IRC bertanggung jawab untuk menentukan kualifikasi penerima dan jenis bantuan yang sesuai berdasarkan latar belakang masing-masing penerima sehingga bantuan tersebut dapat digunakan untuk memenuhi kebutuhan mereka. Penelitian ini bertujuan untuk menilai potensi zakat dalam mengembangkan kualitas umat Islam di Malaysia dengan menyoroti praktik setiap IRC dalam mendistribusikan bantuan kepada setiap penerima zakat yang berkualitas. Statistik distribusi dan bentuk program yang disediakan oleh IRC dianalisis secara deskriptif untuk melihat potensi zakat itu sendiri secara praktis dalam meningkatkan kualitas umat Islam. Studi ini menemukan bahwa IRC telah menyediakan berbagai program yang bertujuan untuk meningkatkan kualitas asnaf melalui distribusi ekonomi yang merata, distribusi kesejahteraan sosial, produksi sumber daya manusia dan peningkatan pendidikan. Dengan demikian, setiap Muslim, terutama pembayar zakat, harus mengambil kesempatan untuk secara setara terlibat dengan IRC untuk memastikan bahwa dana zakat dapat dioptimalkan untuk pengembangan umat Islam di Malaysia.Kata kunci: Zakat, Pengembangan Manusia, Pengumpulan, Distribusi, IRC